DSN MUI DAN OTORITAS JASA KEUANGAN SERTA PEREKONOMIAN (STUDI LITERATUR DAN FENOMENOLOGI) - Arivatu Ni’mati Rahmatika; Septian Ragil Anandita (Fakultas Ekonomi dan Bisnis, 2018)
DSN-MUI produces fatwas to control Islamic Microfinance activities so that theyalways remain in the Islamic rules called Sharia Compliance, then OJK produces rules torun the activities according to the functions of Islamic Microfinance. Both have a role inthe economy through the creation of rules in the implementation of the functions ofIslamic Microfinance, namely savings and loan services. The aims to be achieved in thisresearch is to uncover and describe how the role of DSN-MUI through its fatwa and OJKthrough its regulations in order to improve the economy as indicated by GDPcalculation. This study uses a qualitative approach with literary studies andphenomenology studies as the object of study. By using this method, this study resulted inthe conclusion that the DSN-MUI and OJK must play a role together to improve theeconomy, through Islamic Microfinance products that are channeled to MSMEs as wellas people in need in the form of loans, keep economic activities going which isautomatically said that the economy will increase due to activities that are notconstrained by capital.